Comparative Study of Convectional Slab, Flat Slab &Post-Tensioned FlatSlab on Etabs Software - Shweta Mandloi, Anurag Tripathi (International Journal of Advanced Science and Technology, 2020)
Abstract The post-tensioning method is now a day’s increasing widely, due to its application. By using post-tensioning method one can design the most economic and the safe design. While using this method more precautions has to be made for shear and deflection criteria for the slabs.In a developing country like India the benefits of post stressing and particularly of Post-Tensioning are yet to be recognized. In the present study an attempt is made to compare the cost effectiveness, Durability, Quality, sustainability of Post- Tensioned flat slab systems with respect to reinforced concrete flat slab system. The purpose of this research paper new construction technology issues in India and find out causes, severity, effects to adopt changes. The research should be pave a road for implement changes in construction projects techniques and mitigate it’s affects in cultural and organization changes in firms to increase profitability, compete with their rivals and control project to minimize cost and schedule overrun. This research paper is focused on comparative study of Conventional slab, flat slab and post-tensioned flat slab. In this paper, an attempt has been made to compare the study between Conventional slab, flat slab, and post -tensioned flat slab for G+10 story building with different span length. This type of slab has been analyzed and designed by Etabs software